Menjaga Keutuhan Rumah Tangga pada Masa Pandemi Covid 19 di Wilayah Kelurahan Ciluar Kecamatan Bogor Utara - Abimanyu Allam; Ahmad Sobari; Suyud Arief (As-Syar'i: Jurnal Bimbingan & Konseling Keluarga, 2022)
The advent of the covid pandemic 19 has had a dramatic negative impact on all aspects of life especially economic ones, which also result in domestic breakdown. Because not a few households are devastated by the covid 19 plague, but many families are able to preserve their families intact in the midst of the covid 19 plague. The appearance of the covid 19 plague presents a test and hindrance to all especially those who have gone from the household in order to preserve the home intact and to continue to promote family harmony. In the above phenomena it is the study to analyze and observe a family capable of well managing the well-being of the covid 19th pandemic in the region of the cilgor north district. The study is a study that USES a qualitative descriptive approach with a field research type, which directly observes the covid 19th plague of the family and can still preserve the intact and harmonious integrity of the household. The writer also went directly to the families to interview how their efforts to preserve the intact of the covid 19 pandemic. As for the results of this study, the efforts or tip of the family in the region of cilgor north bogor in preserving the unity of his household during the pandemic of covid 19. The efforts of one family to preserve the integrity of the home varied so much at its heart they faced the difficult times of the covid 19 pandemic by ever drawing closer to god, always being grateful for god's gifts, and sticking to one another's commitments. Key words: always keep home united and harmonious family